2018
DOI: 10.1161/atvbaha.118.311814
|View full text |Cite
|
Sign up to set email alerts
|

V-ATPase (Vacuolar ATPase) Activity Required for ABCA1 (ATP-Binding Cassette Protein A1)-Mediated Cholesterol Efflux

Abstract: Objective We have shown that ABCA1 mediates unfolding of the apoA1 N-terminal helical hairpin during apoA1 lipidation. Others have shown that an acidic pH exposes the hydrophobic surface of apoA1. We postulated that the vacuolar ATPase (V-ATPase) proton pump facilitates apoA1 unfolding and promotes ABCA1 mediated cholesterol efflux. Approach and Results We found that V-ATPase inhibitors dose dependently decreased ABCA1 mediated cholesterol efflux to apoA1 in baby hamster kidney (BHK) cells and RAW264.7 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Next, we tested whether CADs disrupted the H + gradient across the lysosomal membrane. Employing pH-sensitive (fluorescein isothiocyanate [FITC]) and pH-insensitive (tetramethylrhodamine [TMR]) dextrans as a pair of ratiometric sensors that reflect the relative lysosomal pH, 39 we demonstrated that terfenadine and ebastine significantly increased the lysosomal pH within 1 h ( Figure 2 E). Consistently, the fluorescence intensity of LysoTracker green that accumulates in lysosomes and other cytoplasmic acidic organelles was reduced significantly upon 1 h treatment with CADs ( Figure 2 F).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we tested whether CADs disrupted the H + gradient across the lysosomal membrane. Employing pH-sensitive (fluorescein isothiocyanate [FITC]) and pH-insensitive (tetramethylrhodamine [TMR]) dextrans as a pair of ratiometric sensors that reflect the relative lysosomal pH, 39 we demonstrated that terfenadine and ebastine significantly increased the lysosomal pH within 1 h ( Figure 2 E). Consistently, the fluorescence intensity of LysoTracker green that accumulates in lysosomes and other cytoplasmic acidic organelles was reduced significantly upon 1 h treatment with CADs ( Figure 2 F).…”
Section: Resultsmentioning
confidence: 99%
“…Future work should determine the impact of inflammation on regulators of lysosomal function and lipid homeostasis under normo- or hyperlipidaemic conditions. These processes should be investigated in parallel as we found evidence that inflammatory induced lysosomal dysfunction and intracellular lipid homeostasis seem to be tightly connected especially since a recent study demonstrated vATPases to be of crucial importance for ABCA1-mediated HDL efflux [70] , a process known to be impaired in psoriasis patients as well. [12] Future therapeutic strategies could address lysosomal re-acidification as a mechanism by which to ultimately decrease CVD risk in chronically inflamed patients.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, RNA-Seq analysis found ABCA1 as one of the most highly downregulated transcripts (log fold 2.95 (OVCAR3) and log fold 2.1 (OVCAR8)). ABCA1 is a target known to be directly affected by V-ATPase inhibition [ 50 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%